2016
DOI: 10.1037/hea0000314
|View full text |Cite
|
Sign up to set email alerts
|

Macro-level implicit HIV prejudice and the health of community residents with HIV.

Abstract: Objectives This study examined how community levels of implicit HIV prejudice are associated with the psychological and physical well-being of people with HIV living in those same communities. It also examined whether community motivation to control prejudice and/or explicit HIV prejudice moderates the relationship of implicit prejudice and well-being. Methods Participants were 206 people with HIV living in 42 different communities in New England who completed measures that assessed psychological distress, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
20
0
1
Order By: Relevance
“…Aggregated social norms have been used in previous research to measure contextual features of stigma and prejudice across a range of groups, including Blacks, 42 immigrants, 43 sexual minorities, 44 and people with psychopathology, 45 and HIV/AIDS. 46,47 This work has shown that community-level prejudicial attitudes are associated with self-stigma, 45 disclosure concerns, 46 psychological distress, 48 poor self-rated health, 49 and even shortened lifespans, 42 among the stigmatized.…”
Section: Structural Stigmamentioning
confidence: 96%
“…Aggregated social norms have been used in previous research to measure contextual features of stigma and prejudice across a range of groups, including Blacks, 42 immigrants, 43 sexual minorities, 44 and people with psychopathology, 45 and HIV/AIDS. 46,47 This work has shown that community-level prejudicial attitudes are associated with self-stigma, 45 disclosure concerns, 46 psychological distress, 48 poor self-rated health, 49 and even shortened lifespans, 42 among the stigmatized.…”
Section: Structural Stigmamentioning
confidence: 96%
“…Thus, experienced stigma in the community can increase levels of psychological distress (i.e., anxiety and depression) among PLWH. 24 In the current study, we expect that the specific health effects of experienced stigma differ depending on the source or context (i.e., healthcare providers and staff versus the community).…”
Section: Introductionmentioning
confidence: 93%
“…In general, these adverse effects are expected to operate whether the stigmatized condition is visible (eg, race/ethnicity) or concealable (eg, asymptomatic HIV) [ 23 , 24 ]. Several studies have also examined the health and behavioral impacts of social norms [ 25 - 31 ], but few studies in the literature on HIV stigma have directly connected the two constructs [ 29 , 32 , 33 ]. In a well-designed US study of persons with concealable stigmatized identities such as mental illness and family health problems, Quinn and Chaudoir [ 17 ] examined how both anticipated stigma and social norms (described in their article as “cultural stigma”) were associated with psychological distress.…”
mentioning
confidence: 99%